2006
DOI: 10.1017/s0265051705006741
|View full text |Cite
|
Sign up to set email alerts
|

Taking the plunge: The hopes and fears of students as they begin music college

Abstract: The attitudes and experiences of 13 music students entering a conservatoire were tracked before their entry and throughout their first term at college. Aspirations and apprehensions towards the musical, academic and social aspects of college life were collected in addition to career aims, and the data analysed qualitatively to produce emergent themes. Three pivot points were drawn from the analysis, describing events or factors that appear to shape the development of the students as musicians. The first highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 10 publications
5
51
0
1
Order By: Relevance
“…Some of the most notable macro transitions that occur during many musicians' early adulthood are those associated with gaining admission to an institution, such as a music academy or conservatoire, with the intention of studying to become a professional musician and those associated with negotiating the passage from such study to working life (see MacNamara et al 2008MacNamara et al , 2006. With respect to the transition into study Burt and Mills (2006), have argued that, in order to help students manage this transition smoothly, we need to understand the multiple tensions and conflicts that music students encounter and struggle with. For example, notions of personal competence as compared to other students, and managing relationships with others, pose substantive challenges for students early in their advanced music studies (for example Burt and Mills 2006;Kingsbury 1988).…”
Section: Musicians and Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most notable macro transitions that occur during many musicians' early adulthood are those associated with gaining admission to an institution, such as a music academy or conservatoire, with the intention of studying to become a professional musician and those associated with negotiating the passage from such study to working life (see MacNamara et al 2008MacNamara et al , 2006. With respect to the transition into study Burt and Mills (2006), have argued that, in order to help students manage this transition smoothly, we need to understand the multiple tensions and conflicts that music students encounter and struggle with. For example, notions of personal competence as compared to other students, and managing relationships with others, pose substantive challenges for students early in their advanced music studies (for example Burt and Mills 2006;Kingsbury 1988).…”
Section: Musicians and Transitionsmentioning
confidence: 99%
“…With respect to the transition into study Burt and Mills (2006), have argued that, in order to help students manage this transition smoothly, we need to understand the multiple tensions and conflicts that music students encounter and struggle with. For example, notions of personal competence as compared to other students, and managing relationships with others, pose substantive challenges for students early in their advanced music studies (for example Burt and Mills 2006;Kingsbury 1988). Juuti and Littleton (2010), in their study exploring the significance of entering the music academy, also underscored the challenge of reconciling what is personally meaningful with the collective space of cultural forms and social relations whilst negotiating membership of the established music culture.…”
Section: Musicians and Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burt and Mills (2006) investigated 13 college music majors and found that they tended to cite the importance of the first performance after entering their schools of music; feedback about the first performance greatly influenced their confidence. Thus, to obtain positive feedback, music majors have been found to place emphasis on improved performance levels and prioritization of private lessons and personal practice (Kostaka, 2002;Wolfgang, 1990;Teachout, 2001).…”
Section: Perceptions and Experiences Of Music Students In Us Highermentioning
confidence: 99%
“…There were 15 questions concerning the perceived factors: (1) 3 questions on language, including 1 written language question (Green, 2007;Ying, 2003) and 2 conversational language questions (Barratt & Huba, 1994;Fu, 1995;Macrae, 1997;Williams, Woodhal, & O'Brian, 1986), (2) 4 questions concerning social support network (Kagan & Cohen, 1990;Perrucci & Hu, 1995;Yeh & Inose, 2003), 3) 5 questions concerning connectedness to the host culture, including familiarity with the American school system (Day & Hajj, 1986;White, Brown, & Suddick, 1983), relationships with American friends (Kagan & Cohen, 1990), and relationships with professors (Burt & Mills, 2006;Williamon & Thompson, 2006), 4) 2 questions concerning Asian learning styles (Niles, 1995;Leung, 2001;Yee, 1976), and 5) 1 question concerning emotional stability (Schram & Lauver, 1988;Wan, Chapman, & Biggs, 1992;Yeh & Inose, 2003).…”
Section: Measurement Instrumentmentioning
confidence: 99%